A water-repelling investigation of 300–450 kg/m3 density porous silicate concrete - Laukaitis, Antanas; Dudik, Aleksandr (Journal of Civil Engineering and Management, 1996)
This paper deals with porous silicate convert voluminous water—repellence treatment technological parameters and properties using bitumen emulsions. Bitumen emulsions were prepared using laboratory equipment made up of two electrically heated tanks for bitumen and emulsifier. The melted bitumen solution was added at an even rate to a mixer (3000 rpm). The bitumen emulsion temperature was 80–85 °C. The emulsifying agent used for rapidly decomposing emulsions (decomposition up to 5 min) was sulphate soap and naphthenate soap EGIK-3, for medially decomposition after 5-10 min)—crude residue from petroleum refining, slowly decomposing emulsions (decomposition after move than 10 min)—sulphite liquor residues. Composition of bitumen emulsions: bitumen BND 60190 47,9%, water 47,6%, emulsifier 3,45-3,81%, trisodium polyphosphate 0,95-0,60%, washing soap (70%) 0,40-0,29%. The bitumen emulsion decomposition time was determined by mixing it with finely milled inert filler until the bitumen forms a “ball”. Formation mixture composition: activation degree – 22%, water/solids ratio V/K – 0,6, amount of aluminium powder – 0,25% based on solids, bitumen emulsion – 1, 3, 5, 10% based on solids and calculated as bitumen mass, hydrothermic treatment conditions 1,5+8+1,5 h at 0,8 MPa vapour pressure. Water absorption was determined using standard methods by immersing samples in water and using artificial rain (1,5—2 mm/mm). Bitumen emulsion additives have an influence on the formation mixture consistency and maximum mass temperature. The formation mixture consistency also depends on the nature of the emulsifying agent used (Fig. 1) slowly decomposing emulsions, made with sulphite liquor residue, slow down the formation mixture blowing and that is why it is necessary to heat water to increase the mortar temperature to 36 °C (Fig. 2). Medially and rapidly decomposing bitumen emulsions do not greatly decrease the mass blowing (Fig. 3, curve 3) and correspondingly increase the sample density (Table 1). Bitumen emulsion additive has also an effect on calcium hydrosilicate phase composition. Sample chemical (Table 2), thermic and roentgenogram analysis indicate that the control sample cementation material is CSH(I) (Fig. 4, curve 1). 1% bitumen addition does not change the calcium hydrosilicate phase composition. A 3–5% bitumen addition in porous silicate concrete samples lower the amount of SiO2 combined into calcium hydrosilicates and at the same time the C/S ratio increases, while there is a decrease in the general amount of cementation materials (Table 2). A 5–10% bitumen addition changes the phase composition of cementation materials radically, alongside CSH(I) and α-C2S appears, which is showed by endothermic peak at 455—470°C (Fig. 4, curve 4, 5) and diffractive lines 0,242, 0,353, 0,421 nm (Fig. 5, curves 4, 5). The decrease in cementation material is explained by the quartz granule and hampers the SiO2 reaction with CaO. For this reason there is a decrease in sample compression of bitumen lower the compression strength only by 17–22%. Water absorption data in Fig. 7 was determined using a rapidly decomposing water-proofing bitumen emulsion. 1% absorption addition lowers the sample’s water absorption by 2,6–3,0 times (Fig. 7 a, b curves 1, 2). A 3–5 % bitumen addition decreases water absorption by 3,0–4,0 times (Fig. 7 a, b curves 3, 4). The use of bitumen emulsion changes the nature of water absorption. If control samples after 1 h absorbed all the water amount, the samples with bitumen additive absorb only 20–40% of the amount. When slowly and medially decomposing bitumen emulsions are used, the water absorption is the same (Fig. 8, 9). On the average, bitumen emulsions decrease the water absorption by 2–3 times. An increase in bitumen over 1% is not favourable, because water absorption changes insignificantly. Investigations using artificial rain give lower sample water absorption (Fig. 8, 9 curves 1, 2). Water-proofed 450 kg/m3 porous silicate concrete with bitumen emulsion were used during construction of 7 one- storey houses in Vilnius, Trakai and Salcininkai districts, where this porous concrete approved itself fully. It was determined, that 300–450 kg/m3 porous silicate concrete water-proofing with bitumen emulsion is purposeful. When medially and rapidly decomposing bitumen emulsions are used, the silicate mortar fluidity increases and the blowing decreases and that is why heated water needs to be used for mixing. Bitumen additives up to 3% do not have any influence on calcium hydrosilicate phase composition. When larger amounts of bitumen (5–10%) are present, alongside CSH(I), α-C2S is formed and the total amount of calcium hydrosilicate decreases. In this case the bitumen forms a film which covers the quartz grains. 1% bitumen addition decreases the sample strength by 17–22 %, but bitumen emulsions are efficient additions and lower the porous silicate concrete sample water absorption by 1–3 times. 300–450 kg/m3 tankio dujų silikatbetonio hidrofobizacijos tyrimai Santrauka. Nagrinėjama dujų silikatbetonio tūrinė hidrofobizacija bitumo emulsijomis. Ištirta formavimo mišinio konsistencijos priklausomybė nuo bitumo emulsijos bei naudoto emulsiklio rūšių. Nustatyta bitumo emulsijų įtaka formavimo mišinio išsipūtimui ir masės temperatūrai. Išnagrinėta bitumo kiekio įtaka fazinei kalcio hidrosilikatų sudėčiai, gaminių tankiui ir jų stipriui gniuždant. Nustatyta, kad 1% bitumo priedas 2–3 kartus sumažina dujų silikatbetonio vandens įgeriamumą, kad bituminės emulsijos yra efektyvūs dujų silikatbetonio hidrofobizatoriai. Article in Russian. First Published Online: 26 Jul 2012